DEVELOPMENT OF STRATEGIC ENVIRONMENTAL ASSESSMENT (SEA) IN SCIENCE LEARNING - Ahmad Khoiri, *Widha Sunarno, Sajidan, Sukarmin (International Journal of Advanced Science and Technology, 2020)
This study aimed to developing valid and reliable instruments to identify the Environmental Awareness (EA) profile of Senior High School students using Strategic Environmental Assessment (SEA) adopted from Fischer. Methodology: The research method used types of Research and Development (R&D) with 6 stages, namely: (1) Initial research (2) Needs Analysis, (3) Literature studies, (4) Theoretical products, (5) Expert validation, and (6) Individual tests. Data collection using SEA instruments and observation, analysis techniques V-Aiken and t-test using Lisrel 8.8 Second-Order Confirmatory Factor Analysis (CFA). Main Findings: Based on the analysis of the data that; 1) The evaluation of the SEA Instrument in the Validation of Content V-Aiken stated 30 items were valid; 2) Analysis of the results using a CFA Second-order Lisrel produces; a) Model fit at P-value of 0.25> 0.05. RMSEA of 0.095 and NFI of 0.67; b) The loading factor values on indicators A1, A3 and A5 <0.5, indicators A2, A4 and A6> 0.5; c) T-value <1.96 so that it meets the T-value significance criteria limits. The results showed the SEA instruments with indicators Careness (EA1), Courisity (EA2), Critical (EA3), Dependability (EA4), Responsibility (EA5), Wisdom (EA6) were declared valid, reliable and could be used to measure EA of Senior High School students. Application of this study: This study applies to Senior High School students. Novelty/Originality of this study: a) The SEA instruments to identify caring, critical attitudes and environmental awareness of students on science issues that are developing in the community. B) The accuracy Environmental Awareness profile using SEA Instrument based valid, reliable and model fit criteria.